Gender Perception: Study of Students' Perceptions of the Electronic Module Linear Equations Mathematics and Physics I - Astalini Astalini; Dwi Agus Kurniawan; Darmaji Darmaji; Shella Maryani (STKIP Singkawang, 2022)
This research was conducted to answer how students' perceptions based on gender towards the E-module of Mathematical Physics I. The research methodology used a quantitative research type which was analyzed using descriptive and inferential statistical analysis techniques. Technique sampling used a purposive sampling technique with the criteria that students were or had followed the physics mathematics course. The sampel is using of 60 students. With data collection the instrument used was a student perception questionnaire. By using the T test results in class A sig.2 tailed value of 0.728> 0.05. Whereas in class B found a sig.2 tailed value of 0.034 <0.05, this can be concluded that there is a significant (real) difference between students' perceptions of the E-Module Mathematical Physics I. It is hoped that the Flip PDF Proffesional researcher will conduct an in-depth analysis of the relationship between gender and perception. on other Mathematical Physics materials I.